Abstracts of the 1st International Online Conference on Functional Biomaterials - Pankaj Vadgama (Materials Proceedings)
The 1st International Online Conference on Functional Biomaterials (IOCFB2024) was held from 10 to 12 July 2024. The conference covered a wide range of implantable biomaterials development topics, such as drug delivery, tissue engineering, antibacterial, dental, bone, and therapy. It sought to advance fresh approaches to the development of clinical biomaterials and broaden the scientific perspectives of biomaterials scientists. In order to foster interactions without the constraint of location or travel restrictions, the conference adopted an open online forum. Oral and poster presentations were featured in live broadcasts, enabling participants to take part in interactive discussions and sessions.